Measuring Preservice Mathematics Teachers’ Technological Pedagogical and Content Knowlede in the Post-Pandemic Era - Aini, Afifah Nur; Masrurotullaily (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Technological Pedagogical and Content Knowledge (TPACK) represents the essential knowledge that teachers must master. TPACK consists of seven dimensions: Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK) and the integration of all these in Technological Pedagogical and Content Knowledge (TPACK). During the COVID-19 pandemic, lectures were shifted online, significantly impacting the TPACK development of pre-service math teachers. This research aims to contribute to the existing literature by examining how online lectures during a pandemic influence the TPACK of pre-service teachers. The study involves assessing the TPACK of 129 pre-service teachers who participated in both online lectures and offline Field Introduction of School activities. A sample of 39 students was selected using stratified random sampling. Data collection instruments included a self-assessment questionnaire, three open-ended questions answered by students, and performance assessments completed by tutors. Despite the challenges posed by online lectures during the pandemic, students demonstrated a good overall proficiency in TPACK, with Technological Knowledge (TK) exhibiting the highest achievement. However, other dimensions of TPACK showed weaker performance, likely due to obstacles encountered during online learning, such as difficulties in delivering material and engaging in online microteaching practices.